2015
DOI: 10.1007/s10195-015-0354-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of bone quality of the first and second sacral segments amongst trauma patients: concerns about iliosacral screw fixation

Abstract: BackgroundIliosacral screw fixation has become a common method for surgical stabilization of acute disruptions of the pelvic ring. Placement of iliosacral screws into the first sacral (S1) body is the preferred method of fixation, but size limitations and sacral dysmorphism may preclude S1 fixation. In these clinical situations, fixation into the second sacral (S2) body has been recommended. The objective of this study was to evaluate the bone quality of the S1 compared to S2 in the described “safe zone” of il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…A subgroup analysis showed similar results. These findings corroborate the earlier results by Salazar et al [20] in a study of 25 normal sacra in which S2 was 28.1% less dense. Further analysis of our results showed that density was highest in the anterior and lateral ROIs of S1.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…A subgroup analysis showed similar results. These findings corroborate the earlier results by Salazar et al [20] in a study of 25 normal sacra in which S2 was 28.1% less dense. Further analysis of our results showed that density was highest in the anterior and lateral ROIs of S1.…”
Section: Discussionsupporting
confidence: 93%
“…A Hounsfield unit value for each sacral segment was then calculated adapting the methodology from Salazar et al [20]. For each sacral segment, four circular regions of interest (ROIs) were strategically placed utilizing the axial CT sections (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors compared trajectory-specific ROI analysis in L1-L5, again finding that the CBT ROIs were consistently denser via HU analysis than traditional pedicle tracts. 68 Salazar et al 69 performed a similar analysis of screw trajectories at S1 and S2 in 25 consecutive trauma patients. Their intent was to shed light on whether placing iliosacral screws through S1 versus S2 made any difference.…”
Section: Resultsmentioning
confidence: 99%